2016
DOI: 10.4236/as.2016.75028
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients Flow as Affected by Cropping System and Production Niche in Smallholder Farmers of Cyabayaga Watershed

Abstract: Nutrient-balance assessments are valuable tools for both planning and monitoring the implementation of sustainable integrated soil fertility management strategies. The aim of this study was to assess nutrient flows as affected by cropping systems and production niche in soils of Cyabayaga watershed. yabayaga watershed is located in Nyagatare district, Eastern province of Rwanda. Production niches considered are homestead fields, remote hillside fields and wetland fields. Partial nutrient (N, P and K) flows wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Furthermore, this study discovered that smallholder farmers prioritize soil fertility management for crops with high monetary value (84). According to our findings, the staple and monetary value of crops for smallholders varied by country and region within the same country based on agro-ecological characteristics.…”
Section: Socio-economic Attributes On Soil Fertility Managementmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, this study discovered that smallholder farmers prioritize soil fertility management for crops with high monetary value (84). According to our findings, the staple and monetary value of crops for smallholders varied by country and region within the same country based on agro-ecological characteristics.…”
Section: Socio-economic Attributes On Soil Fertility Managementmentioning
confidence: 62%
“…Similarly, Haileslassie et al (68) found that in Ethiopia, crops with high monetary value, such as teff and wheat, receive more attention than crops with low profitability. Positive nutrient balances (particularly N, P, and K) were observed in Rwandan fields with high-value crops such as rice, banana, and tomato, whereas negative nutrient balances were observed in fields with maize, sorghum, cassava, onions, and ground nuts (84).…”
Section: Socio-economic Attributes On Soil Fertility Managementmentioning
confidence: 95%
“…The mean full N, P and K nutrient balances of the three wealth groups in this study were similar to several research findings conducted in smallholder farming systems, which suggested that most Ethiopian soils have a negative N and K nutrient balances (Table 4). Similarly, Kabirigi, Musana, Kagabo, Mukuralinda, and Nabahungu (2016) reported a negative N and K nutrient balances in a study conducted in smallholder farms and semi-arid tropical region in Rwanda (Table 4). Moreover, this study is in line with most studies carried out in smallholder farming systems in Africa that showed a negative N and K balances (Bahr et al, 2014;van Beek et al, 2009;Guillermo et al, 2010;Kabirigi et al, 2016).…”
Section: Nutrient Balancesmentioning
confidence: 86%
“…Similarly, Kabirigi, Musana, Kagabo, Mukuralinda, and Nabahungu (2016) reported a negative N and K nutrient balances in a study conducted in smallholder farms and semi-arid tropical region in Rwanda (Table 4). Moreover, this study is in line with most studies carried out in smallholder farming systems in Africa that showed a negative N and K balances (Bahr et al, 2014;van Beek et al, 2009;Guillermo et al, 2010;Kabirigi et al, 2016). This indicated that there is N depletion in both study sites and K nutrient depletion in Raya Azebo, while for P, the trend was less pronounced.…”
Section: Nutrient Balancesmentioning
confidence: 86%
“…Rwanda's soils need chemical fertilizer inputs since some parts of the country are characterized with low quantity of inorganic matter like nitrogen, sulfur, phosphorus and potassium along with the regular popular use of organic manures which are low in nutrient content (Ministry of Agriculture and Animal Resources, 2009, 2018). In studied areas, in Rwanda, soil fertility was imbalanced and caused low yields in maize and groundnuts (Kabirigi et al, 2016). So frequent and intensive application of necessary fertilizers (N, P, and K) is to be encouraged, and it has started with distribution of agro-chemicals fertilizers rich in the organic nutrients to the local farmers to support one cow per low-income family program which involves distributing heifers to needy families and ensuring the use of both natural organic nutrients and agrochemicals for better yields of food crops by smallholder farmers (Ministry of Agriculture and Animal Resources, 2009Resources, , 2018.…”
Section: Soil Infertility and Crop Nutrient Deficiencymentioning
confidence: 98%